Glass-Embedded Fan-Out Antenna-in-Packaging for 5G Millimeter Wave Applications - Liu, Chia-Hao; Chung, Hsien; Lu, Ren-Kai; Lwo, Ben-Je; Ni, Tom; Pan, Alice (International Journal of Integrated Engineering, 2022)
The paper proposes a novel Antenna-in-Packaging (AiP) structure design for 60 GHz, millimeter wave WiFi applications. In the AiP design, single- or double-sided glass redistribution layers were embedded in a typical fan-out (FO) packaging structure to introduce design flexibility and to improve the radiation properties of the antenna. ANSYS-HFSS software was employed for electromagnetic (EM) characteristic simulations on the fan-out AiP (FO_AiP) design. To improve antenna radiation performance, single factor analyses were first performed to study the impact of each of the design parameters. A consecutive procedure followed to find more suitable combinations of the design parameters. As a result, two typical glass-embedded FO_AiP structures - one with 7.6 GHz bandwidth plus 4.7 dB gain and upward radiation, and another with 5.3 GHz bandwidth plus 5.2 dB gain and downward radiation, are proposed for the 60 GHz applications.